Estimating the Contribution of Selected Risk Factors in Attribut-able Burden to Stroke in Iran - A Bahadori Monfared; H Soori; M Karami (Tehran University of Medical Sciences, 2012)
Background:Knowledge of the magnitude of avoidable burden by risk factors is needed for health policy,priority setting,and preventing stroke.The aim of this study was to estimate the contribution of selected risk factors including hypertension,overweight,obesity, tobacco use,and physical inactivity to the attributable burden of stroke in Iran.Methods:The World Health Organization Comparative Risk Assessment(CRA) methodology was employed to calculate the Potential Impact Fraction (PIF) and percentage of avoidable burden of stroke, which attributed to its risk factors among Iranian adults in 2009. Prevalence of risk factors was obtained from the 5th STEPS survey of chronic disease risk factors which conducted in 2009. PIF was estimated on both theoretical minimum and feasible minimum risk. A simulation procedure incorporating sources of uncertainty was used to estimate the uncertainties for the attributable burden.Results: About 15.7%(95% uncertainty intervals: 5.8- 23.5)of attributable Disability Adjusted Life Years (DALYs)to stroke in adult males and 15.8% (95% uncertainty intervals: 5.8- 23.5)in adult females are avoidable after changing the current prevalence(16.0% and 16.1% for males and females,respectively) of hypertension to 10% in both sexes.Conclusion:This work highlighted the important role of hypertension and overweight.Accordingly,policy makers are advised to consider these risk factors once implementing interventional program in Iran.